Effect of Instructor-Personalized Multimedia in the Online Classroom - Mandernach, B. Jean (International Review of Research in Open and Distributed Learning, 2009)
There is considerable evidence that well-designed multimedia resources can enhance learning outcomes, yet there is little information on the role of multimedia in influencing essential motivational variables, such as student engagement. The current study examines the impact of instructor-personalized multimedia supplements on student engagement in an introductory, college-level online course. A comparison of student engagement between courses that feature increasing numbers of instructor-personalized multimedia components reveals conflicting evidence. While qualitative student feedback indicates enhanced engagement as a function of instructor-generated multimedia supplements, quantitative data reports no significant differences in engagement or learning between the various levels of multimedia inclusion. Findings highlight the complexity surrounding the appropriate use of multimedia within an online course. University policy-makers and instructors are cautioned to examine carefully the cost-benefit ratio of multimedia inclusion for online learning environments.